2021
DOI: 10.51519/journalisi.v3i3.163
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation of Information and Communication Technology for Environmental Sustainability: A Global Perspective

Abstract: There has been a rapid development of Information and Communication Technologies (ICTs) globally, and ICT have been used as a tool to attain environment sustainability all over the world. There are diverse environmental challenges faced by developing countries such as ecosystem deterioration, pollution, resource depletion, loss of biodiversity and climate change and the management of above problems is difficult because they involve multiple actors and its occurrence is over time and space. Environmental Scient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…An alternative refrigerant gas leak detection system is presented to reduce human intervention and boost confidence in the system in case of leakage and by using experimentation cycles including factors of the industrial environment, product, and a thermographic camera with infrared technology to get the dataset, regression logistic method performed the best in predictions, demonstrating that automatic decision-making in an industrial environment concerning gas leaks [12]. Intelligent models are robust and have reduced the average time to leak detection by a tangible percentage for all the intelligent models compared to a real-time transient model in literature and all had a time savings of 25% to 48% [13].…”
Section: Introductionmentioning
confidence: 87%
“…An alternative refrigerant gas leak detection system is presented to reduce human intervention and boost confidence in the system in case of leakage and by using experimentation cycles including factors of the industrial environment, product, and a thermographic camera with infrared technology to get the dataset, regression logistic method performed the best in predictions, demonstrating that automatic decision-making in an industrial environment concerning gas leaks [12]. Intelligent models are robust and have reduced the average time to leak detection by a tangible percentage for all the intelligent models compared to a real-time transient model in literature and all had a time savings of 25% to 48% [13].…”
Section: Introductionmentioning
confidence: 87%
“…They discovered that, above a certain degree of educational achievement, the substantial influence of poverty on climate change can decrease. Additionally, some recent research looks at the direct connection between pollution discharges and environmental deterioration and education [ 37 , 38 ]. As a result, since they support renewable energy, human resources, physical education, and educational status all help to construct the EKC and reduce air pollution.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Still, it may cut carbon emissions and EC in other areas of the economy, such as transportation, intelligent buildings, and cybernetic work and knowledge. ICT and carbon emissions were inspected by Owuru et al [ 18 ]. According to the opposing idea of how ICT influence carbon emissions, this study found an inverted relation between ICT and carbon emissions.…”
Section: Introductionmentioning
confidence: 99%